The Study of the Paleoclimatic Situation and the Problem of Population Mobility in the Eurasian Zone of the 10th -5th Centuries. BC. - Yeranyan, Nzhdeh (History and Culture, 2022)
Various natural phenomena, including climate change and various social manifestations resulting from them, have been in the focus of attention of specialists in various fields in recent decades. Despite the available research, the works on climate change in the Armenian Highlands to a lesser extent present the broad issues of the relationship between society and nature, expressed in climate change, such as the movement of societies over a large area and the change in their way of life. The purpose of this study is to present climatic changes in some zones of Eurasia at the end of the 2nd and the beginning of the 1st millennium BC. and consider their influence on the movements of different tribes and cultures. Studies show that over the past 5000 years, the Eurasian zone of interest to us has experienced several cooling events, which in turn led to over-humidification. In other words, in the Eurasian zone at the end of the 2nd millennium BC. a situation of natural conditions was created, when the extraction of food became difficult. Therefore, it is quite logical that the tribes living in those areas, together or separately, had to leave their settlements in the hope of finding more favorable conditions. Probably, climatic changes were also the reason that, judging by the archaeological material, some tribes, which were characterized by a new economy and culture, settled almost throughout the Caucasus. The combination of written and archaeological sources suggests that a special role among them was played by tribes known in professional literature as "Cimmerian and Scythian tribes".